Ochrobactrum anthropi induced retropharyngeal abscess with mediastinal extension complicating airway obstruction: A case report. - Al-naami, A.; Khan, L.; Athlawy, Y.; Sun, Zhonghua (John Wiley & Sons, 2014)
Retropharyngeal abscess with involvement of mediastinal abscess represents an uncommon complication of upper respiratory tract infections. We report a case presenting with a large retropharyngeal abscess with airway obstruction as the primary presenting symptom. Contrast-enhanced CT showed a large retropharyngeal abscess in the neck with extension to the upper and posterior mediastinal spaces. The abscess was surgically excised with 200 cc pus drained from the neck and mediastinal regions. We describe this case to assist physicians in making the difficult diagnosis when confronting a patient with airway obstruction, as early recognition of retropharyngeal abscess permits emergent airway management.